Using Machine Learning to Measure Changes in Cable News Coverage of Immigration (2014-2019) - Krupenkin, Masha; Rothschild, David (Computation + Journalism Symposium 2020, 2020)
Did media coverage of immigration change after Donald Trump entered the Republican race, and again after he was inaugurated as President? We apply automated text analysis to every cable news segment since 2014 for Fox News and CNN (and since 2015 for MSNBC) and identify over 60,000 cable news segments about immigration. We examine both the selection into coverage of immigration and determine whether news frames about immigration shifted during and after the 2016 presidential campaign. We find that the volume of immigration coverage on Fox News nearly doubled after the 2016 election, as compared to more modest rises on MSNBC and CNN. We also find striking growth in the use of the crime frame in immigration coverage, with one out of every eight immigration news segments mentioning crime. Finally, we find that media discussions of immigration policy shifted to the right, eschewing traditional debates over comprehensive immigration reform in favor of more punitive measures. These findings have important implications for public attitudes towards immigrants in the era of Trump.